2020
DOI: 10.3390/md18030165
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenes and Cyclodepsipeptides from Marine-Derived Fungus Trichoderma longibrachiatum and Their Antagonistic Activities against Soil-Borne Pathogens

Abstract: Soil-borne pathogens, including phytopathogenic fungi and root-knot nematodes, could synergistically invade vegetable roots and result in serious economic losses. The genus of Trichoderma has been proven to be a promising reservoir of biocontrol agents in agriculture. In this study, the search for antagonistic metabolites from a marine-derived fungus, Trichoderma longibrachiatum, obtained two structural series of sesquiterpenes 1–6 and cyclodepsipeptides 7–9. Notably, the novel 1 was a rare norsesquiterpene ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 38 publications
(45 reference statements)
0
39
0
1
Order By: Relevance
“…The fungus T. longibrachiatum is generally isolated from terrestrial soil and plants and has broad-spectrum and potential antagonistic effects in inhibiting the growth of plant pathogenic fungi [14][15][16][17]. In terms of the antifungal compounds derived from T. longibrachiatum, it has been reported that a new rare norsesquiterpene exhibited a potent antagonistic ability against Colletotrichum lagenarium, C. fragariae, carbendazim-resistant strains of Botrytis cinerea, and Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungus T. longibrachiatum is generally isolated from terrestrial soil and plants and has broad-spectrum and potential antagonistic effects in inhibiting the growth of plant pathogenic fungi [14][15][16][17]. In terms of the antifungal compounds derived from T. longibrachiatum, it has been reported that a new rare norsesquiterpene exhibited a potent antagonistic ability against Colletotrichum lagenarium, C. fragariae, carbendazim-resistant strains of Botrytis cinerea, and Fusarium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the antifungal compounds derived from T. longibrachiatum, it has been reported that a new rare norsesquiterpene exhibited a potent antagonistic ability against Colletotrichum lagenarium, C. fragariae, carbendazim-resistant strains of Botrytis cinerea, and Fusarium spp. [15]. However, there is still a lack of papers describing the in vitro and in vivo antifungal activities of secondary metabolites produced by T. longibrachiatum against plant diseases caused by fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Some of t he compounds contained in T. longibranchiatum extract have been researched. Extract of ethyl acetate from marine-derived fungus T. longibrachiatum from Jiaozhou Bay, Qingdao, Chi na contained two st ructural series of sesquiterpenes and cyclodepsipeptides, both have antifungal activity (Du et al, 2020). Other studies reported that the extract of ethyl acetate of T. longibrachiatum associated with the sponge Haliclona sp.…”
Section: Days Of Incubationmentioning
confidence: 99%
“…Thus far, scientists have isolated numerous natural products with antitumor, antibacterial, and other biological activities from marine organisms [ 12 , 15 , 16 , 17 , 18 , 19 ]. Modern pharmacological studies also demonstrate that many marine biological metabolites show good effects on killing phytopathogenic bacteria, which possibly can be used for developing biological fungicides [ 20 , 21 , 22 , 23 , 24 ]. In fact, at the present, marine organisms have become an important resource for developing new biological fungicides to control plant diseases.…”
Section: Introductionmentioning
confidence: 99%